Physical and Numerical Modelling of Post-Pumping Seawater Intrusion - Leonard Stoeckl; Marc Walther; Leanne K. Morgan (Geofluids)
This paper explores post-pumping seawater intrusion (PP-SWI), which is the phenomenon of seawater intruding further inland than the location of a well, after pumping has ceased. Despite numerous papers on the topic of seawater intrusion and pumping, this is the first time that PP-SWI has been described in the literature, to our knowledge. This paper describes a laboratory-scale investigation of the phenomenon and we demonstrate that PP-SWI can be reproduced within physical experiments. We also show, using numerical modelling, that PP-SWI is caused by disequilibrium in the flow field following the cessation of pumping. Specifically, in our simulations, the cone of depression persisted after the cessation of pumping (first moving inland and then retreating toward the coastal boundary) which caused a lag in the reestablishment of fresh water flow toward the coast, after pumping had stopped. It was during this period of flow-field disequilibrium that PP-SWI occurred. We expect systems with larger postextraction disequilibrium to be most susceptible to PP-SWI and recommend future research to improve understanding of the relationship between hydrogeological parameters, extraction rates, well location, and incidence of PP-SWI. In those systems where PP-SWI is most likely, quantitative analysis of groundwater extraction and SWI will need to employ transient approaches to ensure that SWI is not underestimated.